2020
DOI: 10.1021/acsabm.9b01079
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Fe/N-Doped Hollow Carbon Nanospheres with Multienzyme Mimic Activities against Inflammation

Abstract: Inflammation, including infectious and noninfectious inflammation, are a growing threat to public health worldwide. For different types of inflammation, more specific and intensified therapy is needed. Nanozymes are able to regulate levels of radical reactive oxygen species (ROS) to suppress inflammation, becoming potential anti-inflammatory agents. Herein, hollow porous carbon spheres codoped with nitrogen and iron (Fe/N-HCNs) are synthesized through a one-pot strategy, which exerted multienzyme mimicking act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…It seems that the Fe- and N-co-doped carbon materials can significantly enhance the bactericidal effect of hydrogen peroxide, even if its concentration is much lower than that used for clinical purposes [ 31 ]. If the bacteria are exposed solely to the external H 2 O 2 , or solely to the Fe/N-co-doped carbon, survival rates are high [ 4 ]. A comparison of the oxidase- and peroxidase-like activities of Fe–N–C materials showed that the oxidase-like activity is inferior to peroxidase-like activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems that the Fe- and N-co-doped carbon materials can significantly enhance the bactericidal effect of hydrogen peroxide, even if its concentration is much lower than that used for clinical purposes [ 31 ]. If the bacteria are exposed solely to the external H 2 O 2 , or solely to the Fe/N-co-doped carbon, survival rates are high [ 4 ]. A comparison of the oxidase- and peroxidase-like activities of Fe–N–C materials showed that the oxidase-like activity is inferior to peroxidase-like activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…and macroscopic objects such as porous macroparticles). Summarizing, only a few studies investigating the possible antibacterial properties of Fe-doped carbon materials have been reported so far, and in most of them the addition of H 2 O 2 is used as an external, artificial source of ROS simultaneously with the studied Fe-doped materials [4]. Simultaneous exposure of bacteria to Fe-doped materials and external (added) H 2 O 2 precludes to indicate unambiguously the factors causing bacterial damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After carbonization at 800 °C for 2 h and NaOH etching at 80 °C for 12 h, the CNSs were obtained. [18,19] Second, FeCl 3 and cysteine were added separately into ethylene glycol containing CNSs to react at 200 °C for 12 h, yielding CNSs@ FeS 2 . As shown via scanning electron microscopy (SEM) (Figure 1a), CNSs@FeS 2 had a regular spherical shape with a ≈200 nm diameter.…”
Section: Characterization Of Cnss@fesmentioning
confidence: 99%